If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 1) = 3x(x + 4) Reorder the terms: 5(1 + x) = 3x(x + 4) (1 * 5 + x * 5) = 3x(x + 4) (5 + 5x) = 3x(x + 4) Reorder the terms: 5 + 5x = 3x(4 + x) 5 + 5x = (4 * 3x + x * 3x) 5 + 5x = (12x + 3x2) Solving 5 + 5x = 12x + 3x2 Solving for variable 'x'. Combine like terms: 5x + -12x = -7x 5 + -7x + -3x2 = 12x + 3x2 + -12x + -3x2 Reorder the terms: 5 + -7x + -3x2 = 12x + -12x + 3x2 + -3x2 Combine like terms: 12x + -12x = 0 5 + -7x + -3x2 = 0 + 3x2 + -3x2 5 + -7x + -3x2 = 3x2 + -3x2 Combine like terms: 3x2 + -3x2 = 0 5 + -7x + -3x2 = 0 Begin completing the square. Divide all terms by -3 the coefficient of the squared term: Divide each side by '-3'. -1.666666667 + 2.333333333x + x2 = 0 Move the constant term to the right: Add '1.666666667' to each side of the equation. -1.666666667 + 2.333333333x + 1.666666667 + x2 = 0 + 1.666666667 Reorder the terms: -1.666666667 + 1.666666667 + 2.333333333x + x2 = 0 + 1.666666667 Combine like terms: -1.666666667 + 1.666666667 = 0.000000000 0.000000000 + 2.333333333x + x2 = 0 + 1.666666667 2.333333333x + x2 = 0 + 1.666666667 Combine like terms: 0 + 1.666666667 = 1.666666667 2.333333333x + x2 = 1.666666667 The x term is 2.333333333x. Take half its coefficient (1.166666667). Square it (1.361111112) and add it to both sides. Add '1.361111112' to each side of the equation. 2.333333333x + 1.361111112 + x2 = 1.666666667 + 1.361111112 Reorder the terms: 1.361111112 + 2.333333333x + x2 = 1.666666667 + 1.361111112 Combine like terms: 1.666666667 + 1.361111112 = 3.027777779 1.361111112 + 2.333333333x + x2 = 3.027777779 Factor a perfect square on the left side: (x + 1.166666667)(x + 1.166666667) = 3.027777779 Calculate the square root of the right side: 1.740051085 Break this problem into two subproblems by setting (x + 1.166666667) equal to 1.740051085 and -1.740051085.Subproblem 1
x + 1.166666667 = 1.740051085 Simplifying x + 1.166666667 = 1.740051085 Reorder the terms: 1.166666667 + x = 1.740051085 Solving 1.166666667 + x = 1.740051085 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.166666667' to each side of the equation. 1.166666667 + -1.166666667 + x = 1.740051085 + -1.166666667 Combine like terms: 1.166666667 + -1.166666667 = 0.000000000 0.000000000 + x = 1.740051085 + -1.166666667 x = 1.740051085 + -1.166666667 Combine like terms: 1.740051085 + -1.166666667 = 0.573384418 x = 0.573384418 Simplifying x = 0.573384418Subproblem 2
x + 1.166666667 = -1.740051085 Simplifying x + 1.166666667 = -1.740051085 Reorder the terms: 1.166666667 + x = -1.740051085 Solving 1.166666667 + x = -1.740051085 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.166666667' to each side of the equation. 1.166666667 + -1.166666667 + x = -1.740051085 + -1.166666667 Combine like terms: 1.166666667 + -1.166666667 = 0.000000000 0.000000000 + x = -1.740051085 + -1.166666667 x = -1.740051085 + -1.166666667 Combine like terms: -1.740051085 + -1.166666667 = -2.906717752 x = -2.906717752 Simplifying x = -2.906717752Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.573384418, -2.906717752}
| 37-4x=9-8x | | 3ln(x^2)=10 | | -4c-2=19 | | 3lnx^2=10 | | 8+4n=-6(-4-n) | | x^3y-4xy=0 | | 5+b= | | 2x+lne^4x=12 | | 2x+lne=12 | | (10*9+5*5)*28=x | | 4(x+2)=2(x+5) | | (10*9+5*5)=x | | 5u-7u=-8 | | 5a^2-8a-31=-10 | | 51ln(1-x)=ln(1-46x) | | (10*8+5*5)*28=x | | -28+7m=-4(4m+7) | | -1=-3/4(m+7) | | x^3-4xy=0 | | -18-11x=36 | | 100-128x=2 | | 8(x-9)=8x+-72 | | 7(6n+7)+8=-195 | | 2x-2a+b=3x+a | | -8(-5-2x)=168 | | 6x+12y-15z= | | 2(2.66)+2= | | s^2-22=112 | | -45-(-59)= | | 8=.35(c+6) | | 10-6(8x-2)=9x-(3+4x) | | 4x+2(7+6x)=142 |